Determination of the Seasonality of Bovine Tuberculosis Disease from the Risk Based Disease Management - Şentürk, Berrin (Journal of Diagnostics, 2017)
This study is among major epidemics in the world and Turkey is conducted to evaluate the seasonality of the risk factors of the disease bovine tuberculosis. The seasonal distribution of Turkey’s outbreak of bovine tuberculosis in the 2005-2014 year was investigated in this study. Office International des Epizooties outbreak data was used to determine Turkey’s monthly bovine tuberculosis outbreak data at the provincial level for this evaluation. Turkey’s 81 provinces, seven geographic regions, and 12-month outbreak data are evaluated. The distribution of the four seasons of the outbreak to the coast and inland are analyzed for the determined seasonality of the disease. In the study, it was found that Turkey reached the highest number of outbreaks of the disease throughout the summer at a rate of 29.44%. In the study, the risk of bovine tuberculosis disease, diseases of the seasonality of the summer months when the investigation come to the fore, has been carefully assessed in terms of planning for disease control measures. As a result, reveals how it should be used in the identification of disease-specific risk that results obtained in the fight against the disease in this study and the importance of the fight against the disease. Taking control of the disease and timely measures for the disease will contribute to the reduction of costs related to the disease.